The trading of space for time under weakly activated catalysis: expeditious synthesis of β-NH2 alcohols via a direct ammonolysis of epoxides with ammonia. Issue 2 (6th January 2023) - Ma, Guolan; Xu, Chang; Yang, Shaoxiong; Zhu, Yanren; Ye, Silei; Qin, Rui; Zeng, Chongchong; Du, Wenqiang; Zhang, Hongbin; Chen, Jingbo
Abstract : The direct synthesis of β-NH2 alcohols via flexible ammonolysis of epoxides is still a challenging and unresolved problem. Abstract : The direct synthesis of β-NH2 alcohols via flexible ammonolysis of epoxides is still a challenging and unresolved problem. Herein, we present a strategy of "trading space for time under weakly activated catalysis" and "shielding the reactivity of the product", and thereby developed a novel single-step ammonolysis reaction of epoxides with ammonia. A stoichiometric amount of HCO2 NH4 as an additive plays a dual role in the global activation of substrates and in completely suppressing the side reaction of excessive alkylation. A broad scope of substrates including terpene- and steroid-derived epoxides cleanly afforded the target β-NH2 alcohols in good to excellent yields under easily adjustable mild conditions. Furthermore, this synthetic protocol is metal-free and eco-friendly and could be used for the gram-scale synthesis of biologically active β-NH2 alcohols that could be converted to diverse functionalized molecules with ease.